Measurement and Numerical Simulation of Ground and Subgrade Vibrations of Beijing Urban Rail Line 13 - Futong Wang; Leilei Yan; Qi Jiang; Xiaxin Tao (Advances in Civil Engineering)
Urban rail transit is an effective way to deal with the problem of traffic congestion in major cities. Trains travel through dense residential and commercial areas, providing convenient transportation while also result in vibration problems in the surrounding environment. Long-lasting vibrations result in disturbance to people’s sleep, malfunction of sensitive equipment, and even damage to heritage buildings. Compared with elevated and tunnel sections, ground surface urban railway generates vibrations and propagates to the surroundings via a more direct path in the form of surface waves, which makes the environmental problem more prominent. Due to the complexity of the train-track-ground system, the characteristics of the vibration propagation and attenuation are yet to be revealed. In this paper, we investigate the vibration of the ground and the subgrade next to the Beijing Urban Rail Line 13 by a field measurement combined with a mathematical model. The duration of ground vibration is divided into two parts: the train passing time and the Doppler effect-related tailing part. Through a regression analysis of the duration, the train passing time is identified and the train traveling speed is estimated. The attenuation relationship of ground vibration intensity is expressed by a piecewise function. In the subgrade, the vibration intensity of particle decays with increasing depth and the stress decay rate is faster than that of the acceleration. The dynamic wheel/rail interaction behaves stationary and periodic, and the magnitude fluctuates up and down with the quasi-static axle weight. The intensity attenuation relationship fitted in this paper provides a basis for designing new lines and renewing old lines and can be used as a reference for the development of vibration-reduction technology. The simulated time history of the wheel-rail force provides an excitation sample for further model experiments and numerical simulation. The proposed train speed identification method may be useful for parameter identification of moving sources such as ships, automobiles, and airplanes.